Realizace podnikatelského záměru ve stavebnictví - Pech, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Hlavní motivací podnikání je tvorba zisku. Pro tvorbu zisku je potřeba mít podnikatelský záměr. Abychom měli úspěšný podnikatelský záměr, musíme jej správně připravit a poté řídit. Celá práce je zaměřená na tvorbu, uvedení na trh a řízení podnikatelského záměru. Na začátku je úvod do prostředí a následně je vše znázorněno na konkrétním případě. Cílem je ukázat, jak postupovat při tvorbě podnikatelského záměru, jaká úskalí mohou nastat a především, jak ze složité situace udělat výhodu.

The main motivation for the business is making profits. For the creation of profit is the need to have a business plan. In order to have a successful business plan, we have to prepare it correctly, and then drive. The entire work is focused on the production, placing on the market and the management of the business plan. At the beginning of the introduction into the environment, and then everything is shown in a particular case. The aim is to show how to do this when you create a business plan, what pitfalls can occur and, above all, from the complex situation do the advantage.
Implementation of the Business Plan in Construction
Keywords: naklady; kalkulace; planovani; controlling; rizeni; cil; průkaz energetické náročnosti budov; podnikatelský záměr; costs; price calculation; planning and scheduling; controlling; management; aim; demonstration of energy performance of buildings; business plan